KORELASI PENERAPAN TEORI KOMPOSISI TARI TERHADAP HASIL BELAJAR KOREOGRAFI PADA MAHASISWA PRODI PENDIDIKAN TARI ANGKATAN 2023 FBS UNIVERSITAS NEGERI PADANG - Jessica Sabrina Utami; Yuliasma (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to identify and describe the correlation between the application of dance composition theory and choreography learning outcomes among students of the Dance Education Study Program, class of 2023, Universitas Negeri Padang. This type of research is quantitative research using the correlation method. The population in this study consisted of all active Dance Education students who had completed the Dance Composition and Choreography courses, from which a sample of 50 students was taken using a purposive sampling technique. Data was collected through objective test and essay instruments to measure the composition theory variable, as well as documentation of project grades for the choreography learning outcomes variable. Data analysis results showed that the students' average theory test score was 75, which is classified into the "Fair" category. Based on the Product Moment correlation test, an r-count value of 0.318 was obtained, which is greater than the r-table (0.279) at a 5% significance level. These findings prove a positive relationship between the mastery of dance composition theory and choreography learning outcomes; thus, the working hypothesis (HI) is accepted. The correlation coefficient within the interval of 0.20–0.399 indicates a level of relationship that falls into the low category. Although dance composition theory is an important main foundation in arranging dance work, there are other factors such as creativity, intuition, and aesthetic experience that also influence students' success in creating choreographic works.